The Effect of Organic Manures, Azotobacter and Spacing on Growth of Solanum nigrum Linn - Kumar, Ashwani; Sharma, Kulwant Rai (Indian Forester, 2015)
The present investigation was carried out in experimental area in Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan during 2004-2006. The study area falls in mid hill zone of HP, where temperature ranges between o 0-36 °C and annual rainfall varies between 1000-1300mm. Seven different treatments viz. T1 (Control), T2 (FYM), T3 (Azotobacter), T4 (FYM + Azotobacter), T5 (Vermicompost). T6 (Vermicompost + Azotobacter) and T7 (Vermicompost + FYM) with three spacings viz. S1 (30x30 cm) S2 (30x45 cm) and S3 (45x45 cm) were studied to observe the impact of these treatments on production parameters. The treatment of vermicompost + Azotobacter combination gave maximum plant height (62.12 cm), number of branches/plant (24.00), number of leaves/plant at flowering stage (200.0), number of fruits/plant (51.21), Maximum values for plant height (55.44 cm), number of branches/plant (21.92), number of leaves/plant at flowering stage (171.0), number of fruits/plant (44.08), were recorded at S3 (45x45 cm) spacing. Overall, treatment of vermicompost + Azotobacter combination at S3 (45x45 cm) spacing gave maximum plant height, number of branches/plant, number of leaves/plant at flowering stage and number of fruits/plant as compared to other treatments at different spacings.